The Effect of Drying Our International Wetland on the Economic and Social Situation of Fishermen Sistan - Hussein Keykha (Journal of Global Pharma Technology, 2017)
Wetland ecosystem is a complex ecosystem and its components great impact chains are accepted and man as part of the ecosystem in the event of any change, it is affected. Therefore, in this study, wetland drying Sistan plain is the result of several years of drought on the lives of fishermen Sistani is studied.Start the Sistan region since 1998 and has been prolonged drought continues. Sistani's 3500 household survey of fishers who were selected sample of 346 questionnaires. Economic and social science experts validity and reliability with Cronbach's alpha and number 747/0 respectively.Data analysis using descriptive statistics including frequency, mean and standard deviation were used. Inferential analysis compared the mean, t-test was performed using spss software and excel% 100 reduction mat weaving in the region, reducing the 82 percent increase in the 64 percent floor multi-job and unemployment is the result of drying wetlands in Sistan fishermen.By reducing fishing areas prone to drying out of wetlands to agricultural and animal husbandry respectively 45 and 40 percent that this reduction is multi-job employment system. Increased eye diseases, respiratory, neurological, psychological, increased insecurity, drug addiction and youth support organizations to increase the number of families covered 76 percent of our wetlands are drying other effects.Keywords: Sistan fishermen, Economic factors, Social factors, Our wetlands.